Implementing adaptation measures for sustainable rice production in Mekong River Delta of Vietnam - Nguyen Hong Son; Le Thanh Tung; Bui Tan Yen; Sebastian, Leocadio S. (2018)
The occurrence of the floods, salinity intrusions and droughts in the Mekong River Delta (MRD) of Vietnam has caused negative impacts to rice production in the region. Annually, high upstream discharge of Mekong River from September to November causes flooding in north-western provinces of the delta. Conversely, low river discharge from January to April causes salinity intrusion in coastal provinces. To address this and prepare for future climate-related risks, the Department of Crop Production (DCP) of the Ministry of Agriculture and Rural Development (MARD) of Vietnam, and the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA) collaborated to implement the climate-related risks maps and adaptation plans (Climate Smart MAP/CS-MAP) for recognizing climate-related risks, identifying potentially affected areas, and developing regional and provincial adaptation plans for rice production. The risk maps and adaptation plans were developed for normal and ENSO (severe) years by using technical data (i.e., topography and hydrology), infrastructures (i.e., dikes, road, and canals), and local experts knowledge. Changing rice-based cropping systems and sowing/transplanting calendars were common adaptive measures proposed by the provinces. The identified options are being integrated in the provincial land use plans and the regional rice master plan. DCP and MARD have issued several directives providing guidance to the provinces to implement the CS-MAP options particularly in adjusting planting time. This poster illustrates the results of CS-MAP implementation in MRD and discusses the potential use of the methodology in other agro-ecological regions and for other agricultural products.